Detection of unmanned aerial vehicle using radio wave scatter on acoustic disturbances of the environment created by aircraft - Kartashov, V.M.; Kharchenko, O.I.; Pososhenko, V.A.; Kolesnik, V.I.; Yegorov, A.B.; Tymoshenko, L.P.; Kapusta, A.I. (Radiotekhnika, 2021)
Unmanned aerial vehicles (UAVs) have recently become widespread, because they are capable of performing a wide range of functions useful for mankind. At the same time, UAVs are a source of potential threats in a number of areas of human activity, namely, military, economic, and everyday life. Therefore, an urgent scientific and technical problem of detecting and observing UAVs has been formed recently to prevent them from performing unauthorized actions. The main means of UAV surveillance are radar (both active and passive), optical, infrared, acoustic stations, as well as complex systems in which joint processing of information obtained using these information channels is carried out. However, in general, the scientific and technical problem of monitoring UAVs, especially small UAVs, remains unresolved: the efficiency of UAV detection using all these methods remains insufficient, and the needs of practice are far from being fully satisfied with the available means. This article is devoted to the analysis of currently known scientific and practical results aimed to assess the possibility of detecting UAVs by radio signals scattered by acoustic disturbances of the environment created by UAVs, and to formulate urgent scientific and technical problems in this aria of knowledge.